Argumentation Practices to Increase Knowledge and Competence of Acid-Base Materials for Prospective Chemistry Teacher Students - Munnal Hani'ah; Nurfina Aznam (Postgraduate, University of Mataram, 2022)
This study aims to determine the practice of argumentation to increase the knowledge and competence of acid-base material for prospective chemistry teacher students. This study uses a quantitative approach with a quasi-experimental method. The design of this research is the pretest posttest group. The sample in this study were 54 students of chemistry education at UIN Sunan Kalijaga Yogyakarta who were taking basic chemistry courses. Meanwhile, the knowledge instrument is in the form of a multiple-choice test, while the competency instrument is a test in the form of a description. The data analysis technique in this study was carried out statistically inferential (analysis of independent sample t-test). The results of the study show thaththere is a significant difference between the pretest and posttest values ​​in the knowledge domain with t value is -5.508 and probability value paired t test is 0.00 (p value < 0.05). In addition, the mean is -4.167 (negative value) indicates that there is a tendency to increase knowledge significantly. There is also a significant difference between the pretest and posttest values ​​of the competency domain with t value is -8.686 and probability value paired t test is 0.00 (p value < 0.05). In addition, the mean is -3,796 (negative value) indicates that there is a tendency to significantly increase the value of the competency dimension.